IMPLEMENTASI PARENTING TERHADAP KEMANDIRIAN ANAK USIA DINI 4-6 TAHUN DI TK SATU ATAP LEBIJAGA - Kajo, Maria Cerlina Isa; Meka, Marsianus; Juita, Angelina Kurnia; Maku, Karmelia Rosfinda Meo (Bunayya, 2026)
This study aims to describe the implementation of a school-based parenting program and the development of independence in children aged 4 to 6 years at the Lebijaga One Roof Kindergarten. The background of this study is based on the finding that several children are still unable to perform daily activities independently, such as putting on shoes, eating without assistance, and tidying up learning equipment. This study uses a qualitative approach with descriptive methods. The research subjects included seven children aged 4 to 6 years, the class teacher, and parents who acted as supporting informants. Data collection techniques were carried out through observation, interviews, and documentation. The data analysis process refers to the Miles and Huberman model, which includes the stages of data reduction, data presentation, and drawing conclusions. The results show that parenting is implemented through habituation of daily activities at school, ongoing communication between teachers and parents, and holding parenting meetings. The research findings also indicate that parenting patterns that provide opportunities for children to try to do activities independently, such as eating alone, putting on shoes, tidying up toys, and preparing learning equipment, can support the development of children's independence. On the other hand, excessive assistance from parents and inconsistent implementation of rules at home can be factors that hinder the development of children's independence.